2013
DOI: 10.1007/s40140-013-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positioning on Cerebral Oxygenation

Abstract: Postural change during anesthesia has a complex effect on the systemic and cerebral circulations which can potentially decrease cerebral blood flow and oxygenation. Cerebral oximetry is emerging as a monitor of cerebral perfusion with widespread application in many types of surgery. The technology is based on the differential absorption of oxygenated and deoxygenated hemoglobin to near-infrared light. However, the dynamic coupling that exists between cerebral arterial, venous and cerebrospinal fluid volumes ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 143 publications
0
3
1
Order By: Relevance
“…In this study, the larger O 2 Hb drop after a supine-stand transition was not accompanied by a larger BP drop, contrary to existing literature [39]. A lower cerebral oxygenation during sitting and standing could be explained by the differences in hydrostatic pressure gradient between the heart and brain in sitting or standing versus supine position, leading to a small but sustained reduction in cerebral perfusion pressure and thus cerebral oxygen delivery [21,40,41]. Because the cerebral metabolic demand and therefore oxygen consumption remain stable, this results in standing O 2 Hb values below and HHb values above baseline.…”
Section: Resultscontrasting
confidence: 81%
“…In this study, the larger O 2 Hb drop after a supine-stand transition was not accompanied by a larger BP drop, contrary to existing literature [39]. A lower cerebral oxygenation during sitting and standing could be explained by the differences in hydrostatic pressure gradient between the heart and brain in sitting or standing versus supine position, leading to a small but sustained reduction in cerebral perfusion pressure and thus cerebral oxygen delivery [21,40,41]. Because the cerebral metabolic demand and therefore oxygen consumption remain stable, this results in standing O 2 Hb values below and HHb values above baseline.…”
Section: Resultscontrasting
confidence: 81%
“…The cerebral blood volume is presumed to increase on the dependent lung side while in the lateral decubitus position. [ 27 ] Blauenstein et al [ 29 ] reported that in healthy right-hand dominant patients, the CBF in the inferior frontal region is higher in the right hemisphere than in the left hemisphere. Although it has been reported that midazolam decreases the CBF in the left prefrontal cortex, we found no evidence that propofol or desflurane affects the laterality of the cerebral blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…The bilateral SjO 2 values did not differ to a statistically significant extent in healthy patients in the supine position; however, postural change during anesthesia, such as adopting the Trendelenburg or beach chair positions, generally affects cerebral circulation. [27,28] In the present study, patients were placed in the lateral decubitus position with bending of the surgical table. The cerebral blood volume is presumed to increase on the dependent lung side while in the lateral decubitus position.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the effect of the drugs administered during general anesthesia in CBF, other events might also alter the blood supply to the brain, as for example patient positioning [92]. Kose at el.…”
Section: Additional Drugs Administered During General Anesthesiamentioning
confidence: 99%